Hydrographic Variability In Bahia Vizcaino, Baja California, Mexico - M Mancilla-Peraza; E Palacios-Hernández; G López-Castillo (Ciencias Marinas, 1993)
The outstanding hydrographic variations in Bahía Vizcaíno, Baja California, were analyzed from temperature, salinity and dissolved oxygen data collected during the ECONER-0391 oceanographic cruise (March 18-22, 1991) and from similar data obtained from a data bank (Banco de Datos e Información Oceanográfica) of the Secretaría de Marina (1960-1968). In winter the vertical distribution of water properties was almost homogeneous and less stable, while in summer it was stratified into three main layers owing to seasonal warming and the annual mean upwelling event. The lower layer had its origin in the Equatorial Transformed Water Mass, which is characterized by Iow dissolved oxygen content (< 3 ml/l). The top layer had higher temperature and dissolved oxygen (> 5.5 ml/l). In general, the intermediate layer or thermocline was associated to a minimum in salinity of Subarctic Pacific Water Mass origin. At the end of the fall the vertical three-layered structure weakened and, during the winter, heat and other water properties were nearly homogeneous in the water column. The propagation of heat from the surface layer and the annual upwelling event controlled the annual variability in temperature in the lower Ievels (>30 m). Consequently, the surface temperature was on phase with the normal annual atmospheric cooling and warming cycle, and lower levels cooled in summer and warmed in winter. The main processes affecting the hydrographic variability in the bay were: the annual upwelling event, the seasonal warming and cooling, the water advection from the upwelling period (September), the convergence of waters to the South of the bay and the intrusions of the Subarctic Pacific Water Mass and Equatorial Transformed Water Mass.